Liver-specific glucagon dysfunction promotes PP-cell hyperplasia and formation of glucagon and PP double-positive cells - Yuko Nakagawa; Takuro Horii; Ayako Fukunaka; Takashi Sato; Zhehao Zhang; Masaki Kobayashi; Tadahiro Kitamura; Yoshitaka Hayashi; Takashi Nishimura; Izuho Hatada; Yoshio Fujitani (PLoS ONE, 2025)
Understanding the mechanisms that regulate cell identity acquisition and cell proliferation is crucial, not only for elucidating cellular functions but also for clarifying the pathogenesis of various diseases, including neoplasms. Pancreatic endocrine cells typically express a single hormone, and their numbers are tightly regulated. Contrary to this general principle, in this study, we found that proglucagon-deficient mice exhibit a significant increase in the number of glucagon (GCG) and pancreatic polypeptide (PP) double-positive cells (GCG+ PP+ cells), together with the hyperplasia of both PP and α cells. Similarly, glucagon receptor-deficient mice displayed PP-cell hyperplasia and an increased number of GCG+ PP+ cells, with PP-cell replication implicated in this process. mTOR signaling was activated in GCG+ PP+ cells, suggesting its involvement in endocrine differentiation. Furthermore, impaired hepatic GCG signaling led to elevated plasma amino acid levels, which in turn promoted pancreatic endocrine cell proliferation and disrupted the maintenance of cellular identity in mice. Moreover, we found that increased glutamine levels promote GCG+ PP+ cell formation via mTOR signaling, revealing a novel regulatory mechanism underlying pancreatic endocrine cell plasticity. These findings provide new insights into endocrine cell regulation, and may contribute to a better understanding of pancreatic neuroendocrine tumor development, as well as the identification of novel therapeutic strategies.